A systematic review of respiratory infection due to air pollution during natural disasters (Medical Journal of Indonesia, 2020)
BACKGROUND Wildfire and volcano eruption occurred in Indonesia due to its geographical location, climate change, global warming, and human behavior. Various substances produced an increased risk of experiencing health problems, including respiratory infection. Evidence about the effect of pulmonary infection during natural disasters is still limited. This study was aimed to review and elaborate on previous studies to determine the effect of air pollution exposure during natural disasters and respiratory infection. METHODS Literature searches were conducted on PubMed, EBSCOhost, and Google Scholar, and was limited to the 10 last years, human studies, and the English language. Inclusion criteria were articles with representation for clinical questions, review articles, population studies, and the full-text article was available. Exclusion criteria were articles that only discussed the exposure to and not the association with the effect of the respiratory infection. The Oxford Center for Evidence-Based Medicine tools appraised six relevant articles. RESULTS Air pollution during a natural disaster enhances particulate matter to 10–70 μg/m3 and more than 5 times the aerosol optical depth measurement compared with the tolerated air concentration. The air level was consistently related to acute respiratory infection, pneumonia, bronchitis, and bronchiolitis admissions in wildfire smoke and volcanic eruption in this review. Nevertheless, there was a diverse result for upper respiratory infection cases. CONCLUSIONS Natural disasters increased the level of ambient air pollution that exceeded the levels recommended by the World Health Organization air quality guideline. Air pollution may play an important role in respiratory tract infection, especially among population with high exposure.